PPAR agonists attenuate lenalidomide's anti-myeloma activity in vitro and in vivo. (1st October 2022) - Sha, Yonggang; Wu, Jian; Paul, Barry; Zhao, Yue; Mathews, Parker; Li, Zhiguo; Norris, John; Wang, Endi; McDonnell, Donald P.; Kang, Yubin
Abstract: Many patients with multiple myeloma (MM) have comorbidities and are treated with PPAR agonists. Immunomodulatory agents (IMiDs) are the cornerstones for MM therapy. Currently, little is known about how co-administration of PPAR agonists impacts lenalidomide treatment in patients with MM. Here, we determined the effects of PPAR agonists on anti-myeloma activities of lenalidomide in vitro and in a myeloma xenograft mouse model. Genetic overexpression and CRISPR/cas9 knockout experiments were performed to determine the role of CRBN in the PPAR-mediated pathway. A retrospective cohort study was performed to determine the correlation of PPAR expression with the outcomes of patients with MM. PPAR agonists down-regulated CRBN expression and reduced the anti-myeloma efficacy of lenalidomide in vitro and in vivo . Co-treatment with PPAR antagonists increased CRBN expression and improved sensitivity to lenalidomide. PPAR expression was higher in bone marrow cells of patients with newly diagnosed MM than in normal control bone marrow samples. High PPAR expression was correlated with poor clinical outcomes. Our study provides the first evidence that PPARs transcriptionally regulate CRBN and that drug-drug interactions between PPAR agonists and IMiDs may impact myeloma treatment outcomes. Highlights: PPAR agonists reduce the anti-myeloma efficacy of lenalidomide in vitro and in a myeloma xenograft mouse model. PPAR agonists directly inhibit gene transcription of CRBN. Co-treatment with PPAR antagonists increases CRBN expression and improves sensitivity to lenalidomide. High PPAR expression correlates with poor clinical outcome in patients with newly diagnosed multiple myeloma.